Gasification of coking wastewater in supercritical water adding alkali catalyst. (13th January 2020) - Chen, Fu; Li, Xiaoxiao; Qu, Junfeng; Ma, Jing; Zhu, Qianlin; Zhang, Shaoliang
Abstract: In this study, the influence of alkali precipitation on the gasification of coking wastewater with KOH as catalyst at 540 °C, 25 MPa was investigated. Adding the KOH increased H2 fraction and the gas yield. The alkali is accumulated in the reactor, and the catalytic effect was further improved with reaction time prolonging. The precipitated alkali in the reactor still showed high catalytic effect on the subsequent gasification of coking wastewater without further adding the alkali. The catalytic activity was slightly reduced owning to the transformation of KOH to K2 CO3 and KHCO3 . A novel 4-lump kinetic model for coking wastewater in SCWG including feedstock, CH4, CO, and CO2 lumps is proposed. The kinetic parameters are estimated for each involved reaction. Highlights: Updated study concerning supercritical water gasification of coking wastewater. Impact of temperature, pressure and residence time on H2 yield. Enhancement of the H2 yield in presence of catalysts via gasification process. A novel 4-lump kinetic model for coking wastewater in SCWG is proposed.